The Effect of Solvency and Profitability on Audit Delay - Sukiranto, Sukiranto; Suhariyanto, Suhariyanto (Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to analyze the effect of solvency and profitability on audit delay in State-Owned Enterprises in the transportation sector listed on the Indonesia Stock Exchange (IDX) during the period 2014–2023, with company size as a moderating variable. This study uses a quantitative method and the data used is Secondary data obtained from annual financial reports and analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach with bootstrapping 5,000 re-samples to test the direct and indirect relationships between variables. The results of the study indicate that only profitability has a significant effect on company size, while the effect of solvency and other variables on audit delay is not significant. This finding suggests that audit time efficiency is more influenced by external factors such as regulatory oversight and governance structure, rather than solely by financial metrics. The insignificance of company size in mediating the relationship between solvency and profitability on audit delay indicates that organizational complexity does not directly lengthen the audit process. This study highlights the importance of strengthening internal control and financial reporting efficiency to speed up audits, and opens up space for further research by including internal oversight variables or industry characteristics as mediators.